2019
DOI: 10.3390/sports7040076
|View full text |Cite
|
Sign up to set email alerts
|

Is the Bike Segment of Modern Olympic Triathlon More a Transition towards Running in Males than It Is in Females?

Abstract: In 2009, the International Triathlon Union created a new triathlon race format: The World Triathlon Series (WTS), for which only athletes with a top 100 world ranking are eligible. Therefore, the purpose of this study was to analyze the influence of the three disciplines on performance within all the WTS Olympic distance races within two Olympic cycles, and to determine whether their relative contribution changed over the years. Methods: For each of a total of 44 races, final race time and position as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 15 publications
4
53
0
Order By: Relevance
“…Linear regressions showed that cycling was the split discipline with the lowest influence on overall performance in an Olympic distance triathlon for both men and women, and that this pattern was similar in the three decades of the WTS circuit. This result corroborates previous studies investigating Olympic distance triathlons [ 2 , 4 ], but was contrary to similar analyses performed for Ironman distance triathlons [ 8 , 10 ]. Race regulations regarding drafting in cycling lead to this outcome, even though cycling comprises a significant percentage of overall race time in every triathlon race distance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Linear regressions showed that cycling was the split discipline with the lowest influence on overall performance in an Olympic distance triathlon for both men and women, and that this pattern was similar in the three decades of the WTS circuit. This result corroborates previous studies investigating Olympic distance triathlons [ 2 , 4 ], but was contrary to similar analyses performed for Ironman distance triathlons [ 8 , 10 ]. Race regulations regarding drafting in cycling lead to this outcome, even though cycling comprises a significant percentage of overall race time in every triathlon race distance.…”
Section: Discussionsupporting
confidence: 87%
“…Olympic distance triathlon (1.5 km/0.93 mile swim; 40 km/24.9 mile cycle; 10 km/6.2 mile run) has become very popular since it debuted at Sydney’s Olympic Games in 2000 [ 1 ]. Its roots date back to 1989 when the International Triathlon Union (ITU) changed the single race Triathlon World Cup to a World Triathlon Series (WTS) annual circuit in 2009 [ 2 , 3 ]. Briefly, from 1989 to 2008, the world championship was a set by a single race.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But despite their low participation numbers in comparison to men, the participation increases in a higher rate than men in all endurance events throughout the years. Moreover, women's endurance performance is also increasing, closing the 2 of 9 performance gap to men in many endurance events, such as open-water swimming [4], Olympic distance triathlon [5], Ironman triathlon [6], and also ultra-triathlons [1].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, successful performance in triathlon is considered to be largely dependent on the ability of an athlete to overcome the specific physiological [5], neuromuscular [6] and biomechanical [7] complications associated with transitioning from cycling to running. Furthermore, recent evidence also suggests that specific effects of the C–R exist between elite male and female triathletes [8]. As a result of the recent increase in the number of short-course events held throughout the 2018/19 International Triathlon Union (ITU) World Triathlon Series (WTS), as well as the advent of the Super League Triathlon series (variable short-course distances), and the inclusion of the mixed relay event at the 2020 Tokyo Olympics, the relative importance of efficiently transitioning from C–R during triathlon, particularly during short-course formats, is re-emphasised and with it, any potential limitations to running performance.…”
Section: Introductionmentioning
confidence: 99%